Impact of pneumococcal conjugate vaccines for children in high- and non-high-income countries - Robert Cohen; Jérémie François Cohen; Martin Chalumeau; Corinne Levy (Taylor & Francis Group, 2017)
Introduction: The high level of effectiveness of pneumococcal conjugate vaccines (PCVs) was demonstrated initially in high-income countries (HICs). However, because the burden of pneumococcal diseases (PDs) is greater in non-high-income countries (NHICs) than HICs, the assessment of these vaccines in this latter setting is crucial. Areas covered: PubMed was used to search for literature related to the effectiveness of PCVs. Several studies described the effectiveness of PCVs in NHICs, and we compare the impact of PCVs on the incidence of invasive pneumococcal disease (IPD) and pneumonia in HICs and NHICs. Expert commentary: Implementation of PCVs has been effective in both HICs and NHICs. The decline in overall incidence of PD is due to the disappearance of most vaccine serotypes, which is straightforward and comparable across the different settings. As expected, the decrease in overall incidence of PD was eroded in part by the increasing incidence of IPD due to non-vaccine serotypes. We need to continue a multi-faceted surveillance of IPD and carriage.